Visualization of the medial forebrain bundle using diffusion tensor imaging - Hana, Ardian; Hana, Anisa; Dooms, Georges; Boecher-Schwarz, Hans; Hertel, Frank (Frontiers in Neuroanatomy, 2015)
Diffusion tensor imaging is a technique that enables physicians the portrayal of white matter tracts in vivo. We used this technique in order to depict the medial forebrain bundle in 15 consecutive patients between 2012 and 2015. Men and women of all ages were included. There were 6 women and 9 men. The mean age was 58,6 years (39-77). Nine patients were candidates for an eventual deep brain stimulation. Eight of them suffered from Parkinson`s disease and one had multiple sclerosis. The remaining 6 patients suffered from different lesions which were situated in the frontal lobe. These were 2 metastasis, 2 meningiomas, 1 cerebral bleeding and 1 glioblastoma. We used a 3DT1-sequence for the navigation. Furthermore T2- and DTI- sequences were performed. The FOV was 200 x 200 mm², slice thickness 2 mm, and an acquisition matrix of 96 x 96 yielding nearly isotropic voxels of 2 x 2 x 2 mm. 3-Tesla-MRI was carried out strictly axial using 32 gradient directions and one b0-image. We used Echo-Planar-Imaging (EPI) and ASSET parallel imaging with an acceleration factor of 2. b-value was 800 s/mm². The maximal angle was 50°. Additional scanning time was less than 9 minutes. We were able to visualize the medial forebrain bundle in 12 of our patients bilaterally and in the remaining 3 patients we depicted the medial forebrain bundle on one side. It was the contralateral side of the lesion. These were 2 meningiomas and one metastasis. Portrayal of the medial forebrain bundle is possible for everyday routine for neurosurgical interventions. As part of the reward circuitry it might be of substantial importance for neurosurgeons during deep brain stimulation in patients with psychiatric disorders. Furthermore it might explain at a certain extent character changes in patients with lesions in the frontal lobe. Surgery in this part of the brain should always take the preservation of this white matter tract into account.